Let Her Speak for Herself: Nineteenth-Century Women Writing on Women in Genesis - Taylor, Marion Ann (Baylor University Press, 2006)
The women of Genesis - Eve, Sarah, Hagar, Rebekah, Leah, and Rachel - intrigued and informed the lives of nineteenth-century women. These women read the biblical stories for themselves and looked for ways to expand, reinforce, or challenge the traditional understanding of women's lives. They communicated their readings of Genesis using diverse genres ranging from poetry to commentary